2015
DOI: 10.1021/acsami.5b09355
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Conductive Polypyrrole Wrinkle Topographies on Polydimethylsiloxane via a Swelling–Deswelling Process and Their Potential Uses in Tissue Engineering

Abstract: Electrically conducting biomaterials have gained great attention in various biomedical studies especially to influence cell and tissue responses. In addition, wrinkling can present a unique topography that can modulate cell-material interactions. In this study, we developed a simple method to create wrinkle topographies of conductive polypyrrole (wPPy) on soft polydimethylsiloxane surfaces via a swelling-deswelling process during and after PPy polymerization and by varying the thickness of the PPy top layers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 61 publications
1
21
0
1
Order By: Relevance
“…This improvement in the Raman enhancement is intimately related to the wrinkled morphology of the substrates, which is in accord with previous reports5152. These hybrid materials are also expected to be applied as transferable biosensors54, photo-catalysts55 and photovoltaic cells56, and a new generation of biomaterials with outstanding comprehensive performances3031.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This improvement in the Raman enhancement is intimately related to the wrinkled morphology of the substrates, which is in accord with previous reports5152. These hybrid materials are also expected to be applied as transferable biosensors54, photo-catalysts55 and photovoltaic cells56, and a new generation of biomaterials with outstanding comprehensive performances3031.…”
Section: Resultssupporting
confidence: 88%
“…Interestingly, it has been identified that surface patterns could greatly enhance the performances (e.g., gas sensing properties) and extend the application fields of CPs2829. For example, patterned CPs films have been used as promising platforms for study of cell attachment and growth, tissue regeneration, and so on3031. Furthermore, novel properties of CPs-based hybrid materials can be obtained due to their coupling effects3233.…”
mentioning
confidence: 99%
“…Therefore, while it is important to construct a variety of biocompatible nanoscale conductive materials at the electrode interface, it is still desired for biomedical applications to provide additional physical guidance cues for cells. When micropatterns are introduced into the bioactive conductive coatings, cellular and supracellular characteristics such as cell morphology and migration, and tissue organization will be influenced, which is necessary for neural electrodes or nerve conduits to create surfaces that can modulate neuron response to the implanted devices [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Surface wrinkling is a physical process that creates unique topographies in nature [5,6]. Nano/microscopic surface reliefs synthesized by wrinkling have been used for nano/microscopic wrinkled surfaces in optical [7] and electronic devices [8], surface-enhanced Raman spectroscopy substrates [9], the realization of tunable wettability [10], and adhesion [11], and cell culture scaffolds [12][13][14][15][16][17]. In the application for cell culture scaffolds, wrinkled surfaces with unique topographies have been used for cell proliferation [12], control of cellular alignment and differentiation [13,14,16], and spheroid generation [15,17].…”
Section: Introductionmentioning
confidence: 99%